Abortion According to Herbal Consume and Parity in the Private Practice Midwife Clinic of Hajjah Gunarti Banjar Baru (Jurnal Ilmu Kesehatan Masyarakat, 2020)
Abortion is a world problem that greatly affects the health, illness and death of pregnant women. The data of the Hj. Gunarti Clinic there were 27 cases of mothers who experienced abortion in 2018, while in 2019, there were an increase of 38 cases. The purpose of this study was to determine the correlation between maternal habits in consuming herbs during pregnancy and maternal parity with the spontaneous abortion prevalence. The research design used is case control, with a ratio of 1:1. There were 38 samples as a cases group and 38 control group samples. The study was conducted at the Private Practice Midwife Clinic of Hj. Gunarti Banjarbaru city, South Kalimantan Province in April to June 2020. The results of the study showed a significant correlation between the habit of consuming herbal medicine with the abortion cases, that mothers with the habit of consuming herbal during pregnancy had a 3.58 times greater risk of having abortion compared to women who did not consume herbal during pregnancy (OR = 3.58, 95% CI: 1.267-10.143, p value = 0.026), and there is a significant correlation between parity and the abortion cases, mothers with high-risk parity (parity> 3) have a risk of 2.95 times greater abortion than mothers with low-risk parity levels ( OR = 2.95, 95% CI: 1.159-7.503, p value = 0.039). It is recommended for health workers to be more active in socializing to the pregnant women not to consume any herbal medicine carelessly, especially those who do not have permit from the drug and food regulatory agencies, so as to avoid the occurrence of unwanted abortion. In addition to that it also further improves the achievements of the family planning program to be able to limit the number of maternal pregnancies in the community.